2003
DOI: 10.1016/s0008-6363(03)00516-9
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases A review of their structure and role in acute coronary syndrome

Abstract: Objective: To summarize the structure, function, and regulation of matrix metalloproteinases (MMPs) and to review the literature to date on their potential role in the pathogenesis of acute coronary syndromes. Methods: A recursive strategy starting with a Medline Search for primary articles in the last decade, followed by identification of additional articles of interest among the cited literature in the primary articles, followed by identification of additional articles of interest cited in the secondary arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
164
2
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(177 citation statements)
references
References 123 publications
2
164
2
9
Order By: Relevance
“…Pathological studies have shown that the expression of several MMPs including MMP-1, MMP-9, MMP-2, MMP-13 and MMP-8 is significantly higher in vulnerable plaques than that in stable plaques (21). Clinical studies have consistently demonstrated that plasma levels of MMP-1, MMP-2 and MMP-9 are significantly elevated in patients with unstable angina or acute myocardial infarction (21). Furthermore, genetic studies have shown that the polymorphisms in the MMP gene promoters are highly related to the incidences of myocardial infarction (8).…”
Section: Discussionmentioning
confidence: 99%
“…Pathological studies have shown that the expression of several MMPs including MMP-1, MMP-9, MMP-2, MMP-13 and MMP-8 is significantly higher in vulnerable plaques than that in stable plaques (21). Clinical studies have consistently demonstrated that plasma levels of MMP-1, MMP-2 and MMP-9 are significantly elevated in patients with unstable angina or acute myocardial infarction (21). Furthermore, genetic studies have shown that the polymorphisms in the MMP gene promoters are highly related to the incidences of myocardial infarction (8).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid-rich atherosclerotic plaques contain abundant oxidized LDL, 28 accumulation of which may induce an inflammatory response leading to the production of proteolytic enzymes, such as matrix metalloproteinases and cysteine proteinases, by activated macrophages. These proteolytic enzymes may play an important role in the outward expansion of the coronary arterial wall, 29,30 and the active biochemical reaction may lead to plaque instability and restenosis after PCI of positive remodeling lesions. 18,19,31,32 Cholesterol crystalli- zation may also be a mechanism of plaque instability in lipid-rich positive remodeling lesions.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that excessive MMP-12 expression exacerbates articular connective tissue and cartilage degradation and thus plays a critical role in the development of Matrix metalloproteinases (MMPs) are a family of zincdependent endopeptidases that possess the ability to degrade all of the extracellular matrix components associated with tissue destruction, and are believed to play important roles in many physiological and pathological processes. 1,2 Among MMPs, MMP-12, also known as macrophage elastase (HME), is the predominant MMP produced by macrophages. 3,4 Accumulating evidence has shown that increased activity of MMP-12 secreted from inflammatory macrophages is associated with several destructive diseases, including atherosclerosis, 5 aortic aneurysm formation, 6 and emphysema.…”
mentioning
confidence: 99%